The Present Perfect Revisited : A Contrastive View - Žic Fuchs, Milena (Array, 2009)
Dahl (1985) quite rightly claims that the perfect in English is one of the most discussed problems in the theory of grammatical categories. Thus, the quantity of literature dealing with the present perfect is impressive to say the least, but what is even more daunting is the lack of agreement on basic issues. Namely, unresolved is the question whether the present perfect is a 'tense' or an 'aspect', as well as the number of uses (rarely 'meanings') the present perfect may have, not to mention the disagreement as to what these 'uses' actually are. Needless to say, the prevailing differences, manifested in grammars and reference books, are not helpful to Croatian speakers trying to master the traditionally 'hard' present perfect which has no direct equivalent in the Croatian language. The present analysis will try to shed light on the present perfect from the basic tenets of Cognitive Grammar (Langacker 1987, 1991, 2001), tenets which primarily stress the inherent meaningfulness of grammatical structure and its symbolic nature. More precisely, a symbolic structure is defined as the linking of a form and a meaning, and meaning is identified with conceptualization in the broadest sense of the word. Thus, elements of grammar are claimed to have meaning and are seen as parts of the continuum made up from the lexicon, morphology and syntax. Following the basic claims of Cognitive Grammar, this analysis will focus on the meaning(s) of the present perfect and how they correlate with notions of 'tense' and 'aspect'. Five hundred sentences containing the present perfect (representative sample extracted from BNC-Baby) will be analysed. The main aim is to see which meanings can be identified, which may be considered to be 'conventionalized', and how they relate to, and possibly resolve, the 'tense-aspect' controversy. Clarifying the status of 'meanings' for the present perfect as well as their relation to 'tense' and 'aspect' is in our opinion fundamental to any attempt of contrasting English and Croatian. In fact this approach will show why previous attempts of contrasting the present perfect which Croatian equivalents proved to be inadequate particularly for further implementation in pedagogical materials of different kinds, and hopefully trigger off a different approach to the contrastive analysis of the present perfect.